Konsep Diri, Pola Asuh Orangtua Demokratis dan Kompetensi Sosial Siswa - Cristiany, Cristiany (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2014)
Abstract. The aim of this research is to know the connection between self concept and education of democratic parents and the students social competence in the students of SMP 20 Surabaya. The sample of this research is students grade VII SMP 20 Surabaya.The regression analyst gives the result :There is a connection between the self concept and education of democratic parents and the students social competence on SMP 20 Surabaya, The value of F = 21,312 on P = 0,00 (<0.01). There is a positive connection between the self concept with the students social competence in SMP 20 Surabaya with the value of t = 3,719 on P = 0,000 (<0,01). There is a significant connection between the education of democratic parents and the students social competence in SMP 20 Surabaya with the value t = 2,919 on P = 0,004 (<0.01). Keywords: Self-concept, Democratic parenting, Social Competence